Linking socio-demographics of meat vendor-processors to residual nitrite in skinless native sausage sold in a typical public market in the Philippines - Obsioma, Virginia P.; Guiral, King Louiegie G.; Matullano, Kathleen R.; Lorilla, Aaron P.; Tagubase, Jackie Lou J.; Calumba, Kriza Faye A.; Sarmiento, Jon Marx P.; Alviola IV, Pedro A. (2020)
Nitrite plays a key preservative role in meat products. However, overapplication could increase the carcinogenicity risks while underapplication could shorten product shelf life. This study aimed to link the socio-demographic profile of the vendor-processors to the residual nitrite levels in skinless native sausage (skinless longganisa) in a typical public market in the Philippines. A total of 90 skinless longganisa packs were collected from the vendor-processors at three times. Skinless longganisa and commercial curing premix samples were analyzed for nitrite levels using the colorimetric method. Utilizing a random effects panel regression model, the impact of socio-demographic factors of the vendor-processors on the application of nitrite in their skinless longganisa products was assessed. The skinless longganisa samples had residual nitrite levels that ranged from 0.005?1.031 mg/kg with a mean value of 0.56 mg/kg of meat, which suggests the underapplication of nitrite at exceedingly low levels (only at most 2% of the recommended amount), compromising the microbial safety of the meat. The number of skinless longganisa vendor-processors with higher educational attainment (p < 0.01 for high school; p < 0.05 for college) was negatively associated with the nitrite content, whereas the frequency of married respondents (p < 0.01) and with more children (p < 0.05) was positively associated with the residual nitrite. Moreover, most of the vendor-processors had insufficient food safety knowledge despite having attended food safety seminars. With extremely low nitrite levels, monitoring and training programs should highlight the importance of applying the recommended levels of nitrite in skinless longganisa as an essential food safety measure.
Includes bibliographical references (pages 1144-1145)
Keywords: Food safety; Longganisa; Nitrite; Panel regression model; Sausage; Vendor-processors.